Implementation of a Digital Platform for Community Participation in Decision Making in Maluku - Putra Mahendra (Asian Digital Governance Problems, 2024)
Purpose: This takes a look at examines the implementation of a digital platform for network participation in choice-making processes in Maluku, Indonesia. Subjects and Methods: Through a stratified random sampling technique and dependent questionnaires, perceptions of members regarding usability, effectiveness, and impact on choice-making were assessed. Statistical analyses, including paired-samples t-checks, regression analyses, and Pearson correlational analyses, have been carried out to perceive great predictors of normal pride and discover relationships among contributors' perceptions and demographic variables. Results: Results imply upgrades in members' perceptions post-implementation, with age and frequency of platform utilization rising as giant predictors of satisfaction. Conclusions: These findings underscore the transformative potential of virtual systems in fostering inclusive governance and sustainable development.